Penerapan Model Discovery Learning (Puzzle) Untuk Meningkatkan Pemahaman Arti Per Kata Alquran Surat Yunus Ayat 40-41 Di Kelas XI IPS 3 SMA Negeri 2 Nganjuk - Indayanti, Rini; Muhyidin, Mohammad; Khasbulloh, Muhammad Nabil (LPTK UIN Syekh Wasil Kediri, 2022)
SMA Negeri 2 Nganjuk is a public school that focuses on learning materials in general subjects. Most of the students who enter and pass the selection at this school come from junior high schools which are also public schools with heterogeneous environmental backgrounds, both in terms of education, religiosity, and economic level. With this diversity, it is certainly not an easy thing as a teacher to teach religious education materials, especially related to the translation of a verse of the Qur'an. In the learning process, the selection of the Discovery learning (Puzzle) model is very necessary in improving the understanding of the meaning per word of the Qur'an Yunus verses 40-41. The purpose of this study was to determine the application of the Discovery Learning (Puzzle) model to improve the understanding of the meaning per word of the Qur'anic verse in the letter Yunus verses 40-41 at SMA Negeri 2 Nganjuk. To achieve the research objectives above, the researcher used the data collection technique used in this study was observation or observation. Research data obtained through observation and documentation, as the subject in this study was class XI IPS 3 with a total of 35 students. Data collection was obtained from research subjects which included test data on student learning outcomes in the form of written tests and skills tests for students to remember and memorize the meaning of words in the Qur'an Yunus: 40-41 which were formed during group demonstrations. The results of the research in the first cycle are that the teacher is less able to manage the class, the discussion does not run optimally, the students are less motivated, because the discussion in the group runs as it is. The results of the research in Cycle II, namely the appropriate learning media will be able to increase the enthusiasm and enthusiasm of students in understanding the subject matter being taught. One of them is the selection of media using this puzzle, it turns out to be very fitting with the material to understand the verse by word of the Qur'an Surah Yunus verses 40-41. Students are classically motivated by experience and learning models that are looking for, matching, and mentioning it again.